Diagnostic Accuracy of Screening Tests for Diabetic Peripheral Neuropathy: An Umbrella Review - María Mogilevskaya; Mariana Gaviria-Carrillo; John Edwin Feliciano-Alfonso; Ana M. Barragan; Carlos A. Calderon-Ospina; Mauricio O. Nava-Mesa (Journal of Diabetes Research)
Peripheral neuropathy is a common cause of morbidity in diabetes. Despite recent advancements in early diagnosis methods, there is a need for practical, highly sensitive, and cost-effective screening methods in clinical practice. This study summarizes evidence from systematic reviews and meta-analyses on the diagnostic accuracy of validated screening methods for diabetic peripheral neuropathy. Two independent reviewers assessed methodological quality and bias using AMSTAR and ROBIS tools. Seven reviews with 19,531 participants were included. The monofilament test showed inconsistent sensitivity (S: 0.53–0.93) and specificity (Sp: 0.64–1.00), along with high variability in its application. Neuropad exhibited high S (86%, 95% CI 79–91). However, variations in the interpretation of results across the included studies may have impacted its Sp (65%, 95% CI 51–76). The Ipswich touch test exhibited adequate diagnostic accuracy (S: 0.77, Sp: 0.96, DOR: 75.24) but lacked comparison with gold standard tests. In vibration perception studies, the biothesiometer outperformed the tuning fork (S: 0.61–0.80 vs. 0.10–0.46). In general, heterogeneity was observed due to varied reference tests, thresholds, and patient differences. The development of automated analysis methods, as well as determination of predictive value of the combination of screening tools, is needed for further studies. Based on the study results, we suggest that clinicians should select screening tools tailored to their patient population, clinical setting, and available resources, as no single test can be universally recommended for all clinical scenarios.